(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Hypertension is a major global health challenge and a leading risk factor for cardiovascular morbidity and mortality. This study provides a comprehensive analysis of the pathophysiology, clinical consequences, and management strategies of hypertension based on recent scientific evidence published between 2022 and 2025. The review highlights the role of vascular dysfunction, neurohormonal activation, and structural remodeling in the development of elevated blood pressure and subsequent target organ damage, including the heart, brain, and kidneys. Both non-pharmacological and pharmacological approaches are evaluated, emphasizing the effectiveness of lifestyle modifications such as dietary regulation, physical activity, and reduced alcohol intake, alongside evidence-based drug therapies. The importance of combination treatment strategies and individualized patient care is also discussed. Additionally, challenges related to resistant hypertension and treatment adherence are addressed. The findings underline the necessity of early diagnosis, continuous monitoring, and integrated management approaches to reduce complications and improve long-term clinical outcomes.